2021
DOI: 10.4314/ovj.v10i4.12
|View full text |Cite
|
Sign up to set email alerts
|

The use of small-bore wire-guided chest drains for the management of feline pyothorax: A retrospective case series

Abstract: Background: Pyothorax in cats is routinely managed, at least initially, with thoracic tube placement associated with systemic antimicrobial administration. Traditionally, large-bore trocar-type thoracostomy tubes have preferentially been used for the drainage of thick material from the pleural space. In recent years, the use of small-bore wire-guided thoracic drains has increased in both small animals and in humans. Few studies have highlighted the efficacy of smallbore wire-guided thoracostomy tubes.Aim: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…However, a canine cadaver study showed no difference in removal of air or low- or high-viscosity fluid between large- and small-bore thoracostomy tubes ( 17 ). This further confirms clinical reports of successful management of pyothorax in dogs and cats with SBWGTT ( 7 , 15 ). Despite the wide use of SBWGTT in dogs and cats for the last decade, limited information exists about associated indications and complications.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, a canine cadaver study showed no difference in removal of air or low- or high-viscosity fluid between large- and small-bore thoracostomy tubes ( 17 ). This further confirms clinical reports of successful management of pyothorax in dogs and cats with SBWGTT ( 7 , 15 ). Despite the wide use of SBWGTT in dogs and cats for the last decade, limited information exists about associated indications and complications.…”
Section: Introductionsupporting
confidence: 88%
“…One case died prior to surgery due to development of septic shock and the second required a lung lobectomy of the perforated lung lobe. Accidental lung perforation with the insertion of the SBWGTT is not previously reported in the previous literature in veterinary medicine ( 6 , 7 , 15 ). Accidental lung laceration associated with placement of thoracostomy tubes is reported in human medicine ( 18 20 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, the needle has a larger outer diameter (10 F) than the tube (8 F), which may promote subcutaneous fluid leakage. A wire-guided technique is described for small-bore tubes (6 F) in 2 case series of cats with pyothorax ( n = 8 [ 8 ] and n = 10 [ 9 ]). These tubes can be placed under sedation using an introducer needle (14 Ga or 18 Ga included in the kit) and a 0.035 inch guidewire [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical large-bore tubes, the use of a 10 F trocar-based thoracostomy tube placed under general anaesthesia is published [ 3 ]. Alternatively, the use of a small-bore (6 F) wire-guided thoracostomy tube is reported in 2 case series of cats with pyothorax [ 8 , 9 ]. The most common complication with these small-bore tubes is a failure to drain, as a result of kinking [ 8 ].…”
Section: Introductionmentioning
confidence: 99%